Calla lily production in enrofloxacin-contaminated soil and manure: An attractive alternative coupling income generation with antimicrobial removal from the environment - Rocha, Camila da Silva; Kochi, Leticia Yoshie; Brito, Júlio Cesar Moreira; Maranho, Leila Teresinha; Carneiro, Daniella Nogueira Moraes; Reis, Michele Valquíria dos; Gauthier, Alexandre; Juneau, Philippe; Gomes, Marcelo Pedrosa (Frontiers in Soil Science, 2022)
Enrofloxacin (Enro) is often detected in soil and animal manure used for crop production and phytotoxic responses have been observed in plants grown under antimicrobial presence. In the present paper, we investigated the effects of the presence of Enro in soils (1.9 mg kg-1) and manure (50.4 mg kg-1) in growth and flower production of calla lily plants (Zantedeschia aethiopica). We also reported the accumulation and distribution of Enro between plant tissues aiming to evaluate the safety of commercializing plants produced under Enro-contaminated conditions. The presence of Enro in soils and manure did not affect plant growth and flower production and did not induce any physiological effects in plants (as evaluated by photosynthetic pigment, hydrogen peroxide concentration, superoxide dismutase and catalase activity in leaves). Plants accumulated Enro mainly in their roots, restraining its translocation to shoots, which contributes to the safety of the commercialization of their flowers. However, when commercialized as pots, the amount of Enro carried by plants is a matter of concern, and therefore, selling pot plants must be avoided. Due to their tolerance and capacity to remove Enro (up to 14.76% of Enro from contaminated soil and/or manure), plants are indicated for phytoremediation programs.